The Influence of Cloud Computing Adoption Interest and Financial Technology Usage on the Performance of Salted-Egg SMEs in Cirebon Regency - Anita Simanjuntak; Irwan Sutirman (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to analyze the effect of interest in adopting cloud computing and the use of financial technology on the performance of salted-egg SMEs in Cirebon Regency. The research background stems from the low level of digital technology adoption among SMEs, despite its potential to improve operational efficiency and financial performance. A quantitative method was applied using a survey approach and multiple linear regression analysis. The population consisted of 50 salted-egg SME owners selected through a saturated sampling technique. The results indicate that interest in cloud computing and the use of fintech have a positive and significant impact on SME performance, both individually and simultaneously, with an R² value of 0.610. These findings suggest that integrating digital technologies can enhance SME competitiveness through more efficient data management and transparent financial transactions. The study contributes theoretically by applying the Technology Acceptance Model and offers practical implications for SME owners and policymakers to accelerate digital transformation.